Criminal Liability for Abuse of Authority of Village Head that Resulted in Corruption Crime - Hendy Iskandar; Ediwarman Ediwarman; Madiasa Ablisar; Mirza Nasution (Locus Journal of Academic Literature Review, 2023)
The village head as the village government, especially in the percut village in the percut sei tuan sub-district, is required to provide sufficient, accurate, timely information to all stakeholders regarding the management of village funds. The purpose of this writing is to find out and analyze the rules of law governing criminal liability for abuse of the authority of the Village Head. The type of research is normative legal research, the research data uses secondary data and is supported by primary data. Data is collected using literature study and interviews. Data analysis was conducted using qualitative analysis method. The results of the study concluded that the legal rules governing criminal liability for abuse of the authority of the village head used in Law Number 6 of 2014 and Law No. 31 of 1999 Jo. Law No. 20 of 2001 and article 374 of the Criminal Code.